Long non‐coding RNA uc.291 controls epithelial differentiation by interfering with the ACTL6A/BAF complex. (4th February 2020) - Panatta, Emanuele; Lena, Anna Maria; Mancini, Mara; Smirnov, Artem; Marini, Alberto; Delli Ponti, Riccardo; Botta‐Orfila, Teresa; Tartaglia, Gian Gaetano; Mauriello, Alessandro; Zhang, Xinna; Calin, George A; Melino, Gerry; et al.
Abstract: The mechanisms that regulate the switch between epidermal progenitor state and differentiation are not fully understood. Recent findings indicate that the chromatin remodelling BAF complex (Brg1‐associated factor complex or SWI/SNF complex) and the transcription factor p63 mutually recruit one another to open chromatin during epidermal differentiation. Here, we identify a long non‐coding transcript that includes an ultraconserved element, uc.291, which physically interacts with ACTL6A and modulates chromatin remodelling to allow differentiation. Loss of uc.291 expression, both in primary keratinocytes and in three‐dimensional skin equivalents, inhibits differentiation as indicated by epidermal differentiation complex genes down‐regulation. ChIP experiments reveal that upon uc.291 depletion, ACTL6A is bound to the differentiation gene promoters and inhibits BAF complex targeting to induce terminal differentiation genes. In the presence of uc.291, the ACTL6A inhibitory effect is released, allowing chromatin changes to promote the expression of differentiation genes. Thus, uc.291 interacts with ACTL6A to modulate chromatin remodelling activity, allowing the transcription of late differentiation genes. Synopsis: The long non‐coding transcript uc.291 contains an ultraconserved region and is upregulated during keratinocyte differentiation. Uc.291 interacts with the BAF‐associated protein ACTL6A to remodel chromatin, promoting late differentiation gene expression. The long non‐coding RNA uc.291 is expressed in the nuclei of differentiated keratinocytes. Depletion of lncRNA uc.291 impairs epidermal differentiation. Uc.291 interacts with ACTL6A allowing BAF‐dependent chromatin remodelling at epidermal differentiation genes. Abstract : The long non‐coding transcript uc.291 contains an ultraconserved region and is upregulated during keratinocyte differentiation. Uc.291 interacts with the BAF‐associated protein ACTL6A to remodel chromatin, promoting late differentiation gene expression.